A local fitting method to improve model calculation accuracy of flow point of asphalt mixture. (25th January 2021) - Zhang, Chao; Tan, Yiqiu; Cyriaque, Assogba Ogoubi; Han, Meizhao; Zhou, Xingye; Meng, Anxin
Highlights: The equivalence of strain method and strain rate method was assessed. A novel method termed local fitting method based on strain rate was developed. A comparison of difference models based on strain method and strain rate methods was performed. Abstract: To accurately determine the flow point of asphalt mixture, the flow number test was performed, and an analysis was conducted on the methods of calculating flow point. Three defects of the existing methods were highlighted, and a novel method termed local fitting method was proposed. The flow number and flow rate were both considered in this research. Strain method and strain rate method were proved to be not equivalent and the extensively employed strain method might present a misleading flow point. In addition, the four-step algorithm of the local fitting method based on strain rate was developed, and the optimal range coefficient K of the present study was calculated as 1.5 based on the alteration trend of flow point. A comparison of the local fitting method and the global fitting method was performed, and significant differences were identified in the fitting curves and calculated results. Moreover, equivalence of Francken and Hoerl strain rate models from the two methods was also assessed, and it was found that significant differences might exist between the two models when using global fitting method, whereas no significant difference was identified based on local fitting method. The novel local fitting method was considered a better analytical procedure to determine the flow point of asphalt mixtures.